Optimising sampling protocols via the heterogeneity test: Challenges in coarse gold mineralisation - Dominy, Simon; Xie, Y. (2016)
Determination of the sampling constant is an important step when applying the Fundamental Sampling Error equation to optimise sampling protocols. The classic method for its determination is based on the heterogeneity test (HT). In coarse gold-dominated mineralisation, the HT sometimes provides an evaluation of the fine-gold background grade population heterogeneity, but understates that of the important high-grade coarse-gold component. This is because the total mass of fragments is too small to represent the full gold particle size distribution of the mineralisation. Despite this, single heterogeneity tests (SHT) are often undertaken on deposits where the presence of coarse gold is ignored, not realised or understated. Resultant sampling and assaying protocols are frequently of poor quality and do not match the mineralisation characteristics. For coarse gold-dominated mineralisation, an empirical approach for sampling constant determination is recommended via direct estimation of the liberation diameter.